Phylogeny of genera in Maleae (Rosaceae) based on chloroplast genome analysis - Sun, Jiahui; Zhao, Dan; Qiao, Ping; Wang, Yiheng; Wu, Ping; Wang, Keren; Guo, Lanping; Huang, Luqi; Zhou, Shiliang (Frontiers in Plant Science, 2024)
In Rosaceae, the replacement of the traditional four-subfamily division (Amygdaloideae or Prunoideae, Maloideae, Rosoideae, and Spiraeoideae) by the three-subfamily division (Dryadoideae, Rosoideae, and Amygdaloideae), the circumscription, systematic position, and phylogeny of genera in Maleae need to be reconsidered.In Maleae, the three-subfamily division (Dryadoideae, Rosoideae, and Amygdaloideae) replaced the traditional four-subfamily division (Amygdaloideae or Prunoideae, Maloideae, Rosoideae, and Spiraeoideae); however, the circumscription, systematic position, and phylogeny of Maleae remain to be established. This The study aimed to circumscribe Maleae, pinpoint its systematic position, and evaluate the status of all generally accepted genera in the tribe using complete chloroplast genome data.Our rResults indicated that Maleae consisted of pome-bearing genera that belonged to Maloideae as well as four genera (Gillenia, Kageneckia, Lindleya, and Vauquelinia) that were formerly considered to be outside Maloideae. The tribe could be subdivided into four subtribes: Gilleniinae (Gillenia), Lindleyinae (Kageneckia and Lindleya), Vaugueliniinae (Vauquelinia), and Malinae (all other genera; the core Maleae). Among the 36 recognized genera, Aria, Docyniopsis, Chamaemespilus, and Mespilus were not considered distinct and more research is needed to determine the taxonomic status of Rhaphiolepis from Eriobotrya. Within the core Maleae, five groups were revealed, whereas Sorbus L. s. l. was split as its members belonged to different groups.